Foamed Cement Properties for Zonal Isolation in Coalbed Methane (CBM) Wells - Irawan, Sonny (2011)
Wells drilled into coal beds for coalbed methane (CBM) generally encounter weaker structures within the beds and have lower fracture gradient as compared to conventional oil or gas wells. CBM is more vulnerable to downhole problems such as lost circulation and formation fracture as the formation cannot withstand a cement density above 11 ppg. Conventional neat cement without light weight additives with average density of 15.9 ppg is not suitable. Foamed cement with a low density of 7-11ppg, high strength per unit volume offers a versatile and economical cementing job. Primary purpose of using foamed cement is to decrease the density of the slurry but here, other advantages have also been identified with applications of this cement. A better understanding on the properties of foamed cement allows the optimization of cement slurry design during its circulation and placement